Traditional use of fish based ethnomedicine in the treatment of some diseases in Eastern Tarai of Nepal - Kumar, Prakash; Verma, Shishir Kumar; Subba, Bharat Raj (Nepalese Journal of Biosciences, 2015)
Nature has provided resources for human beings to use them in manifolds ways making their life to run smoothly in whatever ways they can by preserving the things they use. Fish is an easily available aquatic vertebrate which is of much concerned stuff with rural peoples who not only relish fish stuff but use traditionally whole body of the fish or extract of some parts in the treatment of diseases. Nine species of fish have been recorded in the Tarai region of eastern Nepal to have been used in the traditional medicine for the treatment of diseases.